A case of delivery of a pregnant woman with COVID-19 infection in Daegu, Korea - Jin-Gon Bae; Jin-Kyeong Ha; Myoung Kwon; Hak-Youle Park; Won-Joon Seong; Seong-Yeon Hong (Korean Society of Obstetrics and Gynecology, 2020)
Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is affiliated with the β-coronavirus subgroup, which includes SARS-CoV and Middle East respiratory syndrome coronavirus (MERS-CoV), but is far more infectious than the 2. Because it is potentially life-threatening to infants and pregnant women with weak immune systems, clinical manifestations and vertical transmission of COVID-19 are matters of interest. Staff of the obstetrics department of university hospitals in Daegu and of the Daegu metropolitan government designated Daegu Fatima Hospital for the delivery of pregnant women with suspected and confirmed SARS-CoV-2 infection. Thirteen pregnant women with laboratory-confirmed COVID-19 were identified. Among them was a 28-year-old pregnant woman who had recovered from COVID-19 and had given birth to a healthy girl at 38 weeks of gestational age. We present our uncommon experience with a brief review of literatures.